Zurvanite iconographic canon. Astronomy and mythology - Larichev, V.E.; Parshikov, S.A.; Gienko, E.G. (Archaeoastronomy and Ancient Technologies, 2014)
This article reveals the results of the study of iconographic canon of Zurvanite mythologem belonging to the worldwide myths, comprising the myth of the divine twins. The following reasons make the theme relevant: 1. There is no iconographic canon Zurvanite mythologem which is universally accepted by modern Iranian studies; 2.Saratsk petroglyphic composition of XVIII-XVII centuries BC (Minusinsk Basin of Siberia) in Khakassia that we have defined as the earliest of all supposed images of Zurvanite myth; 3. The significance of Zurvanite myths in the process of monotheistic theology's forming. In our work we have come to the conclusion that the creators of Saratsk petroglyphic composition were the bearers of the Andronovo cultural-historical community who came to the territory of Khakassia in XVIII-XVII centuries BC. In the processes of semantic disclosure of mythologem of the symbols of Saratsk petroglyphic composition due to the fact that Andronovs belonged to the circle of Aryan tribes confederation we relied on the text of the Avesta, Pahlavi texts and medieval authors mentioned in Zurvanite mythologem. Studies have shown that the spatial distribution of Saratsk petroglyphic composition corresponds to the astronomically significant areas of the Saratsky Sunduk sanctuary which is a "classical" Iranian-Aryan vara (protective slab separatings the sacred world from the real world - profane) located on the top of the Saratsky Sunduk mountain. Sacred Astronomy built in the structure of the sanctuary by its creators confirms our assumption of Zurvanite content of Saratsky petroglyphic composition's semantics. In addition the study of the nature of the images of Saratsk composition revealed the principles of "sacred" geometry in the composition structure of Zurvanite iconographic canon.